The Performance of the World Health Organization in Dealing with Covid-19 in the Balance of International Law: Weaknesses and Suggestions for Improving the Organization's Actions - Aramesh Shahbazi; Bassel Abzo (پژوهشهای حقوقی)
The emergence of epidemics and their rapid spread is the result of the nature of international life, which has seen a significant increase in the movement of people and goods. states have realized this issue for a long time, especially after the Second World War, this task was entrusted to the World Health Organization as the guardian of the health and safety of the people of the world. The World Health Organization has faced many challenges during its lifetime, which spans more than seven decades, but the most difficult of these challenges was the Covid-19 crisis. The organization has already tried to deal with this epidemic, and considering that there are 4 million deaths worldwide, it can be described as a failure. This lack of success is rooted in several reasons, which are either related to the structure of the organization or related to its working mechanism. This article is trying to investigate the possible reasons for the failure of the World Health Organization and in this regard, it tries to examine and discuss the necessary solutions to improve the performance of this organization in order to fight against epidemics.